Taken, blessed, broken, and shared: lived experiences of parish catechists teaching religion in public schools - Pedrosa, Edgar; Madrigal, Dennis (Technium Social Sciences Journal, 2024)
Catechists play a significant role in the church’s evangelization. Despite the numerous problems they experienced, they remained faithful to their vocation. Thus, this phenomenological study intends to explore the lived experiences of the parish catechists teaching religion in public schools. Using a purposive sampling method, the data were gathered from six conversation partners coming from the north, south, and central of the diocese through an unstructured in-depth interview. There was only one overarching question and probing questions were asked to cull out significant information. The data were analyzed using recursive textual analysis adopting the framework of Lichtman’s 3C’s. The findings of the study reveal that in teaching religion in public schools, catechists found meaning in their vocation, encountered numerous challenges in their teaching ministry, utilized different strategies in overcoming the challenges, and experienced joy in teaching religion. Generally, they are happy and committed in their teaching ministry despite the challenges they encountered. With these results, full support is necessary to address their needs and to ensure the quality of their teaching performance.